2020
DOI: 10.1371/journal.pone.0228383
|View full text |Cite
|
Sign up to set email alerts
|

Variation in symbiotic N2 fixation rates among Sphagnum mosses

Abstract: Biological nitrogen (N) fixation is an important process supporting primary production in ecosystems, especially in those where N availability is limiting growth, such as peatlands and boreal forests. In many peatlands, peat mosses (genus Sphagnum) are the prime ecosystem engineers, and like feather mosses in boreal forests, they are associated with a diverse community of diazotrophs (N 2-fixing microorganisms) that live in and on their tissue. The large variation in N 2 fixation rates reported in literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
5
9
0
Order By: Relevance
“…The mean BNF rate of 12.2 nmol N gDW ha –1 yr –1 found in laboratory incubations of peat from a forested peatland of Austria with an Nr deposition of 21 kg N ha –1 yr –1 , fell within the range of the BNF rates of peat we found in Fenn’s & Whixall and Migneint (0.3–37 nmol N gDW –1 d –1 ). Looking at the median BNF rates by species (Figure ) we found BNF values close to those reported by van den Elzen et al (2020) from samples collected in different peatland habitats of southern Sweden regarding S. capollifolium subsp. rubellum/ S. fuscum (open bog 0.4–17.5 nmol N gDW –1 d –1 ) and S. fallax (Lagg fen 17.5–66.3 nmol N gDW –1 d –1 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The mean BNF rate of 12.2 nmol N gDW ha –1 yr –1 found in laboratory incubations of peat from a forested peatland of Austria with an Nr deposition of 21 kg N ha –1 yr –1 , fell within the range of the BNF rates of peat we found in Fenn’s & Whixall and Migneint (0.3–37 nmol N gDW –1 d –1 ). Looking at the median BNF rates by species (Figure ) we found BNF values close to those reported by van den Elzen et al (2020) from samples collected in different peatland habitats of southern Sweden regarding S. capollifolium subsp. rubellum/ S. fuscum (open bog 0.4–17.5 nmol N gDW –1 d –1 ) and S. fallax (Lagg fen 17.5–66.3 nmol N gDW –1 d –1 ).…”
Section: Discussionsupporting
confidence: 88%
“…rubellum/ S. fuscum (open bog 0.4–17.5 nmol N gDW –1 d –1 ) and S. fallax (Lagg fen 17.5–66.3 nmol N gDW –1 d –1 ). Across the moss species, S. fallax had the highest BNF rates, which is commensurate with the findings of van den Elzen et al (2020) . Both Sphagnum mosses and peat collected from hollows, had higher BNF rates than species in hummocks (70% and 67%, respectively).…”
Section: Discussionsupporting
confidence: 88%
“…At the same time, elevated nutrient deposition increases the size, activity and diversity of the microbial pool in the acrotelm 24,25 . Lin et al 26 showed P availability imposes a limiting effect on the microbial communities of decomposers and N2 fixers, and there is strong evidence for direct effects of P on N2 fixation rates from fertilisation plots [33][34][35]38 and surface peat measurements 36 . This would accelerate decomposition of the more recalcitrant compounds that usually become buried in the catotelm.…”
Section: Discussionmentioning
confidence: 99%
“…Bogs that accumulate more P are characterised by higher N:C (lower ΔN:C) ratios, indicative of more efficient decomposition. We propose this is a widespread and largely overlooked biogeochemical characteristic of ombrotrophic peatlands, whereby P supply influences the intensity of organic matter decay by promoting N fixation [33][34][35][36][37] and microbial activity [24][25][26] . Furthermore, bogs that experience proportionally greater burial of P relative to N seem to sequester carbon more slowly (r 2 = 0.64, p = 0.003; Figure 4C), showcasing a direct link between nutrient stoichiometry and long-term carbon cycling.…”
Section: Figure 1 Location Of Bog Stoichiometric Profiles and Monitomentioning
confidence: 99%
See 1 more Smart Citation